Conceptual framework to strengthen NIMART implementation in mobile health clinics in eThekwini Municipality, KwaZulu-Natal Province, South Africa. - Ngcobo, Silingene J.; Makhado, Lufuno; Sehularo, Leepile A. (HIV & AIDS Review: International Journal of HIV-Related Problems, 2026)
Introduction: Human immunodeficiency virus (HIV) care within HIV hyperendemic eThekwini municipality remains a public health challenge. Non-availability of any formal framework to support HIV care delivery within the mobile health clinics (MHCs) needed attention. Aim of the study was to develop a conceptual framework to strengthen and improve the utilization and delivery of HIV care within the MHCs of eThekwini municipality. The study was conducted in eThekwini District of Kwa-Zulu Natal Province. Material and methods: An explanatory descriptive simultaneous QUAL+quant+qual multimethod study design was employed on 13 MHCs nurses, 137 MHCs and 12 MHCs managers, preceded by a systematic literature review on HIV care delivery in MHCs and Donabedian's model and Dickoff's theory was adapted for development of the framework following data analysis for individual studies employing descriptive statistics and Atlas. TI respectively. Results: The researchers performed meta-inference and interpreted the qualitative findings from two studies and descriptive results from the quantitative study. Following findings obtained from the systematic review. Multiple themes emerged from the review, operations, and managers suggestive that gross lack of standardized HIV care exists in the MHCs, with multiple challenges spreading across operations and management. While infrastructural challenges exist. Various suggestions also emerged from the study and formed bases for construction of the conceptual framework. Conclusions: The developed NIMART strengthening framework for MHCs addresses current contextual challenges addressing stakeholders, context, dynamics, procedures, and outcomes concerning HIV care in MHCs in line with the universal HIV care and support framework.